2020
DOI: 10.1080/09588221.2020.1744667
|View full text |Cite
|
Sign up to set email alerts
|

A neurocognitive investigation of test methods and gender effects in listening assessment

Abstract: A neurocognitive investigation of test methods and gender effects in listening assessment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 28 publications
4
34
1
1
Order By: Relevance
“…For instance, Chou (2019) investigated whether gender predicted self-efficacy in test preparation for the listening section of the University Entrance Examination test in Taiwan and reported that gender was not associated with self-efficacy, test anxiety, and strategy use. Moreover, Aryadoust et al (2020) conducted a neuroimaging study and employed functional near-infrared spectroscopy (fNIRS) to uncover the test-takers’ neurocognitive mechanisms involved in listening tests. They observed differences in neural substrates across genders, although differences in the test scores of males and females were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Chou (2019) investigated whether gender predicted self-efficacy in test preparation for the listening section of the University Entrance Examination test in Taiwan and reported that gender was not associated with self-efficacy, test anxiety, and strategy use. Moreover, Aryadoust et al (2020) conducted a neuroimaging study and employed functional near-infrared spectroscopy (fNIRS) to uncover the test-takers’ neurocognitive mechanisms involved in listening tests. They observed differences in neural substrates across genders, although differences in the test scores of males and females were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Listening subskills were found to be different in terms of various grain sizes ( Sawaki et al, 2009 ), and the contribution of a particular listening subskill was not consistent across items ( Yi, 2017 ), indicating the vague definition of L2 listening subskills ( Aryadoust, 2020 ). To address this gap, Aryadoust (2020) used the document co-citation analysis to give a systematic review of research on comprehension subskills. An integrative framework of comprehension subskills was provided, which included a total of 18 L2 comprehension subskills.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations